2018
DOI: 10.1039/c7ra13093g
|View full text |Cite
|
Sign up to set email alerts
|

One millimeter per minute growth rates for single wall carbon nanotube forests enabled by porous metal substrates

Abstract: We report an exceptionally high-efficiency synthesis of long single-wall carbon nanotube (SWCNT) forests using a porous substrate (metal meshes) in place of nonporous flat substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…CNT growth rates measured without sulfur addition have diffusion-limited values of 0.2-17 µm s −1[219,220,221,222]. Growth rates of CNTs in direct-spinning systems are not diffusion-limited and a recent paper has shown that S increases the growth rate[223].…”
mentioning
confidence: 99%
“…CNT growth rates measured without sulfur addition have diffusion-limited values of 0.2-17 µm s −1[219,220,221,222]. Growth rates of CNTs in direct-spinning systems are not diffusion-limited and a recent paper has shown that S increases the growth rate[223].…”
mentioning
confidence: 99%
“…It has been previously shown that by using metal mesh substrates, uniform gas delivery could be achieved resulting in the exceptionally high speed synthesis as high as 1 mm/min of SWCNTs and the catalyst-substrate system could be grown for arbitrarily long periods, independent of a fluidization requirement [12]. While this report did demonstrate that a mesh substrate could increase SWCNT yield by ∼8-fold, a single layer would be insufficient for mass production purposes.…”
Section: Introductionmentioning
confidence: 63%
“…In place of silicon substrates, stainless steel (SUS) mesh substrates with aperture size (0.35 mm), wire diameter (0.21 mm) and open porosity of 29.9% and sputtered on both sides were used. This variety was chosen as it was found to be the optimum structure for achieving high efficiency SWCNT growth [12]. It should be noted that the catalyst thickness was chosen because it is well-known to grow SWCNT forests in high efficiency from silicon substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we explored how experimental and simulation data may be combined to understand a typical graphene growth process using the above-mentioned example of the synthesis of adlayer-free and single-crystalline SLG on Cu(111) foils. While there have been previous attempts to simulate reactor conditions for the CVD growth of nanomaterials, ,, to the best of our knowledge, this is the first systematic exploration for 2D materials synthesis. Based on this study, we have identified the different external parameters that typically control the reaction environment and designed a recommended protocol for experimentalists to use to report a process in the literature in a way that will facilitate its reproduction in a different reactor by an interested researcher (Figure ).…”
Section: Introductionmentioning
confidence: 99%